2013
DOI: 10.4103/0970-9371.107512
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular papillary endothelial hyperplasia diagnosed by fine needle aspiration: Report of a case and cytology literature review

Abstract: Intravascular papillary endothelial hyperplasia (IVPEH) is an unusual form of intravascular endothelial proliferation. Fine needle aspiration (FNA) diagnosis of IVPEH is quite challenging and only rare reports of the cytopathological features of this entity have been published. We report a case of a 55-year-old female patient who presented with a mass on her left jaw. FNA of the mass revealed pleomorphic polygonal and spindle cells. A preliminary (onsite) cytological diagnosis of suspicious for malignancy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The cytologic features of IPEH in the published literature show diverse morphologies, leading to frequent diagnostic error. 1 - 3 , 9 , 10 IPEH has been misdiagnosed as malignant vascular tumor, embryonal carcinoma, squamous cell carcinoma, adenoid cystic carcinoma, and giant cell tumor. Handa et al 10 suggested two types of cell populations that can assist in cytologic diagnosis of IPEH: spindle cells and round cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cytologic features of IPEH in the published literature show diverse morphologies, leading to frequent diagnostic error. 1 - 3 , 9 , 10 IPEH has been misdiagnosed as malignant vascular tumor, embryonal carcinoma, squamous cell carcinoma, adenoid cystic carcinoma, and giant cell tumor. Handa et al 10 suggested two types of cell populations that can assist in cytologic diagnosis of IPEH: spindle cells and round cells.…”
Section: Discussionmentioning
confidence: 99%
“…FNA cytology has successfully diagnosed IPEH preoperatively in only 1 reported case. 5 In our patient, preoperative FNA confirmed the presence of a benign lesion; however, surgical excision was needed for definitive diagnosis, emphasizing surgical intervention as both a diagnostic and a therapeutic modality. Prognosis is excellent, and recurrence is rare, typically occurring only in the event of incomplete primary resection.…”
Section: Discussionmentioning
confidence: 59%